GRASSROOTS FEMINIST NETWORKS AND INTERFAITH SOLIDARITY AGAINST RELIGIOUS INTOLERANCE: A DIGITAL ETHNOGRAPHY FROM INDONESIA - Ridho, Akhsin; Damairi, Moh. Uzaer; Matswah, Akrimi (Harmoni, 2025)
This study investigates how grassroots feminist networks in Java confront religious intolerance through digital activism. Amid escalating online hate speech and rising religious conservatism in Indonesia, these networks have strategically mobilized social media to construct counter-narratives that challenge patriarchal and exclusionary religious discourses. Employing digital ethnography, the research analyzed online interactions, campaign materials, and symbolic expressions across feminist platforms from 2020 to 2024. The findings reveal that these networks foster inclusive interfaith alliances and cultivate alternative safe spaces for marginalized voices—particularly women and religious minority groups. While digital platforms offer avenues for empowerment and visibility, activists also contend with backlash in the form of online harassment and ideological suppression. Although the study is limited to digital data and lacks offline ethnographic immersion, it offers original insights into the intersections of gender, religion, and digital resistance in Southeast Asia. It contributes to the growing literature on feminist digital activism and underscores the need for comparative, cross-platform research in future studies.   AbstrakPenelitian ini mengkaji bagaimana jaringan feminis akar rumput di Jawa melawan intoleransi beragama melalui aktivisme digital. Di tengah meningkatnya ujaran kebencian daring dan menguatnya konservatisme di Indonesia, jaringan ini memanfaatkan media sosial untuk membangun kontra-narasi yang menantang wacana patriarkal dan eksklusif dalam agama. Dengan menggunakan etnografi digital, penelitian ini menganalisis interaksi daring, materi kampanye, dan ekspresi simbolik pada berbagai platform feminis sepanjang 2020 hingga 2024. Temuan menunjukkan bahwa jaringan tersebut mendorong aliansi lintas iman yang inklusif serta menciptakan ruang alternatif yang aman bagi suara-suara terpinggirkan, khususnya perempuan dan kelompok minoritas agama. Meskipun platform digital membuka ruang pemberdayaan, aktivis juga menghadapi serangan balik berupa perundungan daring dan penindasan ideologis. Penelitian ini terbatas pada data digital tanpa keterlibatan etnografi luring. Kendati demikian, penelitian ini memberikan kontribusi orisinal terhadap kajian persinggungan gender, agama, dan perlawanan digital di Asia Tenggara, memperkaya literatur tentang aktivisme digital feminis, serta menyerukan studi komparatif lintas platform di masa mendatang.